Assessing the effectiveness of ramp-up during sonar operations using exposure models – a killer whale case study. (abstract): - Benda-Beckmann, A.M. von; Wensveen, P.J.; Kvadsheim, P.H.; Lam, F.P.A.; Miller, P.J.O.; Tyack, P.L.; Ainslie, M.A. (2013)
Ramp-up (or soft-start) procedures are commonly used to mitigate the impact of sound on marine mammals. Although this procedure is often adopted as a common-sense approach, studies that quantify the effectiveness of ramp-up are currently lacking. The effectiveness of ramp-up is investigated by modelling the sound exposure of animals caused by a moving sonar. A naval sonar operation is considered that is preceded by different ramp-up schemes, and the reduction of the area over which hearing threshold shifts are predicted to occur is quantified. The animal behaviour model is based on avoidance responses observed with free-ranging killer whales responding to sonar sounds during controlled exposure experiments. Our simulations indicate that ramp-up procedures can reduce the risk of receiving sound exposure sufficient to induce physiological responses with animals. The predicted effectiveness of the ramp-up procedure was found to depend strongly upon the assumed response threshold and to vary with ramp-up duration. It was found that extending the duration of the ramp-up beyond a few minutes did not add much to the predicted reduction in hearing impact on killer whales, unless a large fraction of animals responds at very low received levels. The main factors that limit the effectiveness of ramp-up in a typical anti-submarine warfare scenario is the combination of high source level, a rapidly moving sonar source, and long silences between consecutive sonar transmissions. The exposure modelling approach can also be used to evaluate and optimize ramp-up procedures for other intense sound sources, such as seismic surveys or pile driving.